Beyond batch experiments: unveiling the potential of bimetallic carbon xerogels for catalytic wet peroxide oxidation of hospital wastewater in continuous mode - Silva, Adriano S. (2024)
Single- and bimetallic carbon xerogels were prepared by incorporating iron and iron-cobalt precursors during their synthesis, respectively, and tested in the catalytic wet peroxide oxidation (CWPO) of ibuprofen spiked into a simulated matrix in batch mode. The bimetallic catalyst outperformed single and non-metallic catalyst by 25 and 85% after 360 min of reaction, at mild temperature (30 °C). The best-performing catalyst was further used to treat hospital wastewater in a CWPO system operating in full continuous mode. Process optimization was carried out considering different catalyst loads, temperatures, and pH. The results obtained showed that the best conditions are initial pH 3, T = 80 °C, and a catalyst load of 35.4 mg cm− 3. Having maintained values of chemical oxygen demand (COD) removals as high as 80% after 24 h of continuous operation, the results herein reported revealed the high potential of the bimetallic carbon xerogel for CWPO of hospital wastewater beyond conventional applications in batch mode. Despite some catalytic deactivation, the bimetallic carbon xerogel still delivered a mineralization degree as high as 55% of the initial total organic carbon (TOC) content of the hospital wastewater in the third 24-h cycle of CWPO in continuous mode of operation with successive catalyst reuse, as opposed to a 73% TOC removal in the first cycle. Therefore, our results open prospects for the implementation of CWPO for hospital wastewater treatment in continuous mode of operation.